An Analysis for the Strategies Development in Developing Moringa Fortification Salt at Sampang District - Dian Farida Asfan; Iffan Maflahah (Agroindustrial Technology Journal, 2021)
Fortification is the addition or enhancement of one or more nutrients into food. Fortification of moringa salt can be used as a business alternative for the people of Sampang, especially salt farmers seeing the selling price of salt which is decreasing from year to year.The purpose of this research is selecting the best strategies development in developing moringa salt at Sampang district . The method for selecting the strategy that will be used in this research is AHP (Analitycal Hierarchy Process) method. The results of data processing using the AHP method resulted in a business development strategy formoringa fortification, namely (1) establishing partnerships with the salt industry to accommodate production products with an eigenvector value of 0.3521; (2) establishing partnerships between land owners, farmer groups and the government to improve processing and marketing capabilities with an eigenvector value of 0.2723; (3) utilizingproduct innovation and institutional asset support with an eigenvector value of 0.2152; (4) producing products in accordance with market standards in order to compete with an eigenvector value of 0.1604